STATUS KERENTANAN NYAMUK Aedes sp. (DIPTERA:CULICIDAE) TERHADAP MALATION DAN AKTIVITAS ENZIM ESTERASE NON SPESIFIK DI WILAYAH KERJA KANTOR KESEHATAN PELABUHAN BANDAR UDARA SAM RATULANGI MANADO - Steven J. Soenjono (POLTEKKES KEMENKES MANADO, 2011)
The aim of this study were determine the susceptibility status of Aedes sp. to malathion insecticide, the elevated to non-specific esterase enzyme activity of Aedes sp, the differences susceptibility status in the Port Health Office working area of Sam Ratulangi Airports Manado. The sample of Aedes sp. eggs was collected from four village in the Port Health Office Working Area of Sam Ratulangi Airport Manado. The research method used was biochemical assay for elevated non-specific esterase enzyme activity and susceptibility testing using the impregnated paper (malathion 0.8%) WHO standard.The results showed the elevated of non-specific esterase enzyme that hydrolyzes the substrate α-naphthyl acetate Aedes sp. in four village In the Port Health Office Working Area of Sam Ratulangi Airport Manado. The percentage of Ae. aegypti resistant to each village is Mapanget Barat 96.7%; Wusa 83.3%; Winetin 73.3%; Lapangan 63.3%. The percentage of Ae.albopictus resistant to each village is Wusa 100%; Mapanget Barat 93.4%; Lapangan 73.3%, Winetin 66.7%. Susceptibility test with WHO standard to Ae.aegypti showing are resistance to malathion with the percentage of death each village 0% (resistant 100%). There are significant differences susceptibility status from the resulting of biochemical test of Aedes sp. in the fourth village.